Mapping Mesoscale Ocean Currents - Zhou, L. (The International Hydrographic Review, 2011)
This paper presents the technical aspects, error analysis and result comparison of a flexible mapping method particularly useful in regional ocean studies. Mesoscale ocean currents are computed from multiple satellite altimeter along-track measurements via objective analysis with a data-derived space-time correlation model. The additional satellite tracks help resolve more eddies with smaller radii and reduce the overall domain-wide mapping errors. The mapping results are consistent with the in-situ hydrographic data and Lagrangian data from a surface drifting buoy. The mapped currents have optimal spatial and temporal resolutions that can benefit the studies of mesoscale variability and surface particle dispersion simulation.